Resepsi kasidah Burdah Al-Bubshiry dalam masyarakat pesatren - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Qashidah Burdah is a religious literary work that got an honor reception from the people around the world. Therefore, it is no wonder that Qashidah Burdah could attract wide interest from the world community in the form of scientific study